(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Cloud computing enables users to use a Web browser only to receive computing services over the Internet. Users just have to pay for the services they are actually using. The present study shows that there is a large gap in the existing system’s security issue. Confidentiality, authentication, access control, and integrity are the main security ideology and one of the most important requirements for any software. This paper investigates existing cloud computing solution for the SaaS model, and explores the various security flaws. The work concludes here with the comparative study of the various existing solutions and addresses the common problems and excuses.